BASIC ASPECTS ENSURING SHIPPING SAFETY - Oleksiy MELNYK; Svitlana ONYSHCHENKO; Oleg ONISHCHENKO; Oleh LOHINOV; Valentyna OCHERETNA; Yurii DOVIDENKO (Scientific Journal of Silesian University of Technology. Series Transport)
Widespread use of innovative technologies in all spheres of life has brought the maritime transport industry, in particular, the process of ship navigation, to a completely new qualitative level. Various navigation systems recently introduced and used only as additional devices have gradually become an obligatory element of shipboard equipment and navigation complexes of modern vessels, extending their functionality and capabilities. The human factor influence caused by automation of ship operation processes becomes a separate challenge. Risks to shipping safety and consequences of breach of safety standards for crew, vessel and cargo are far from being a full list of the problems to be solved. This paper offers an overview of general issues of ensuring the level of safety of shipping, by examining the concept of "vessel safety", considering its individual sides, features, as well as constituent aspects of the concept, systematization of the vessel safety structure to develop solutions toward improving the integral safety and optimization of decision-making in emergencies. Achievement of the general purpose of shipping safety thus means the realization of ways of reducing the influence of the human factor on several accidents and an estimation of the degree of influence of a set of factors on a ship during operation.